Plant extracts used in Brazil for treatment of oral ulcers and mucositis: systematic review - Luiz Evaristo Ricci Volpato; Patrícia Leão Castillo Eubank; Lorraynne dos Santos Lara; Géssica Vasconcelos Godinho; Lucas Guimarães Abreu (Brazilian Dental Science)
Objective: To identify and analyze plant extracts used in Brazil for the treatment of oral ulcers and oral mucositis. Material and Methods: A systematic review was registered in PROSPERO (CRD 42018102184) and performed following the PRISMA protocol. The databases searched were PubMed, Web of Science, Scopus, Lilacs, Scielo, the Brazilian Dentistry Library. Manual searches were also performed. Results: Initially, 440 studies were found, of which 392 were excluded after reading the titles and abstracts. A total of 29 articles were read in full and 11 studies were excluded, resulting in 18 articles included in the systematic review. Nine plant species were identified in five clinical trials and 13 in vivo studies, with Chamomila recutita being the most used (33.3% of the studies). Chamomila recutita showed more promising results for analgesic, anti-inflammatory, and healing properties. Calotropis procera latex significantly decreased (p<0.05) inflammatory mediators, such as TNF-alpha and IL-1beta in oral mucositis induced in rats. Eupatorium laevigatum showed anti-inflammatory activity and analgesic action on oral ulcers. Carapa guianensis Aubl. reduced the severity and painful symptoms of oral mucositis and exhibited better results compared to the use of low power laser. Curcuma longa L accelerated re-epithelialization and resolution of inflammatory processes. Spondias mombin reduced oxidative stress and inflammation caused by oral mucositis and helped on healing it. Extracts of Aloe barbadensis Miller or Aloe vera showed antiinflammatory action but did not help in the healing process of oral ulcers. Copaifera reticulata Ducke oil did not induce improvement in the healing process, nor did it show an anti-inflammatory effect. Malva sylvestris did not show an anti-inflammatory action on oral lesions in humans or rats. The assessment of methodological heterogeneity showed the impossibility of performing a meta-analysis. Risk of bias varied from low to high. Conclusion: The plant species most used and with the best results for the treatment of oral ulcerations and oral mucositis was Chamomilla recutita. Spondias mombin L., Curcuma longa L., Carapa guianensis Aubl and Calotropis procera showed good results in the treatment of oral mucositis, while Eupatorium laevigatum was efficient in the treatment of ulcers of traumatic origin. Malva sylvestris, Copaifera reticulata Ducke, and Aloe barbadensis Miller did not exhibit significant results.